NBS1 interacts with Notch signaling in neuronal homeostasis. Issue 19 (3rd October 2020) - Zhou, Zhong-Wei; Kirtay, Murat; Schneble, Nadine; Yakoub, George; Ding, Mingmei; Rüdiger, Tina; Siniuk, Kanstantsin; Lu, Ruiqing; Jiang, Yi-Nan; Li, Tang-Liang; Kaether, Christoph; Barzilai, Ari; et al.
Abstract: NBS1 is a critical component of the MRN (MRE11/RAD50/NBS1) complex, which regulates ATM- and ATR-mediated DNA damage response (DDR) pathways. Mutations in NBS1 cause the human genomic instability syndrome Nijmegen Breakage Syndrome (NBS), of which neuronal deficits, including microcephaly and intellectual disability, are classical hallmarks. Given its function in the DDR to ensure proper proliferation and prevent death of replicating cells, NBS1 is essential for life. Here we show that, unexpectedly, Nbs1 deletion is dispensable for postmitotic neurons, but compromises their arborization and migration due to dysregulated Notch signaling. We find that Nbs1 interacts with NICD-RBPJ, the effector of Notch signaling, and inhibits Notch activity. Genetic ablation or pharmaceutical inhibition of Notch signaling rescues the maturation and migration defects of Nbs1 -deficient neurons in vitro and in vivo . Upregulation of Notch by Nbs1 deletion is independent of the key DDR downstream effector p53 and inactivation of each MRN component produces a different pattern of Notch activity and distinct neuronal defects. These data indicate that neuronal defects and aberrant Notch activity in Nbs1 -deficient cells are unlikely to be a direct consequence of loss of MRN-mediated DDR function. This study discloses a novel function of NBS1 in crosstalk with the Notch pathway in neuron development.